Protest Paradigm in Indonesia Gelap Coverage: A Comparative Framing Analysis of CNNIndonesia.com and Tempo.co - Ramadhani, Annisa Putri; Ashaf, Abdul Firman; Frasetya, Vito (Universitas Islam Negeri Raden Intan Lampung, 2026)
Indonesia Gelap is a public protest movement against controversial policies during the first100 days of the Prabowo-Gibran administration. Beginning as a digital activism campaign, themovement later evolved into public demonstrations across various regions in Indonesia.Alongside these actions, various media outlets, such as CNNIndonesia.com and tempo.co,published reports. Online media, which normatively serve as sources of information, socialcontrol, and pillars of democracy, in practice have the potential to shape a different reality andinfluence public opinion on an issue. This study aims to examine how CNNIndonesia.com andtempo.co frame their coverage of the Indonesia Gelap movement as a protest, using adescriptive qualitative approach with two stages of analysis: the Pan and Kosicki framingmodel and the McLeod and Hertog protest paradigm analysis. The results indicate thatCNNIndonesia.com tends to adhere to the characteristics of the protest paradigm byemphasizing aspects of conflict, relying on official sources, and engaging in thedelegitimization and demonization of the protests. Meanwhile, tempo.co provides more spacefor the demands and substance of the protests, as well as public support. Adherence to anddeviations from the protest paradigm are influenced by ideology, idealism, interests, and thenature of the protests taking place.